Can major life events explain depressive symptoms? Understanding the mediating role of external shame and fears of receiving compassion - Coelho, Helena Maria Loureiro (2018)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação